Three-layer co-pasting embossed material of light-weight renewable material and preparation process of three-layer co-pasting embossed material

The three-layer co-sticking process is used to process renewable materials to form a lightweight three-layer co-sticking embossing material, which solves the problem of insufficient aesthetics of materials in traditional processes and realizes the reproducibility and green environmental protection requirements of the materials.

CN119840193AActive Publication Date: 2025-04-18SUZHOU GREENTECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411953945.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-18
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

Traditional embossing processes are difficult to effectively deal with renewable materials, resulting in insufficient aesthetics and inability to meet the national green and environmental protection requirements.

Method used

The three-layer co-sticking process is adopted to form an intermediate layer by mixing and foaming the recycled waste with the polyolefin foaming material, and co-sticking and embossing with the surface layer and the bottom layer through heating rollers and embossing rollers to form a three-layer co-sticking embossing material with lightweight renewable materials.

Benefits of technology

It improves the aesthetics and mechanical properties of the material, realizes the reproducibility and lightweight of the material, enhances production efficiency, and meets the national green environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215456920000061
    Figure BDA0005215456920000061
  • Figure BDA0005215456920000071
    Figure BDA0005215456920000071
Patent Text Reader

Abstract

The invention relates to the technical field of material processing and surface treatment, and discloses a preparation process of a three-layer co-pasting embossed material of a lightweight renewable material, and a middle layer of the three-layer co-pasting embossed material is prepared by mixing and foaming a regenerated waste material and a polyolefin foaming material; the method comprises the following steps: S1, carrying out decontamination and drying treatment on a surface layer, a middle layer and a bottom layer, and coating one surface, close to the surface layer, of the middle layer and one surface, close to the middle layer, of the bottom layer with an adhesive; s2, the face, close to the middle layer, of the surface layer and the faces, not coated with the adhesive, of the middle layer and the bottom layer are heated through a heating roller, co-pasting and knurling are completed at the same time through extrusion between a back roller and a knurling roller after heating, and a three-layer co-pasting knurling material is obtained; the method has the advantages that renewable materials can be utilized, and the attractiveness of the embossed materials is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of material processing and surface treatment, and in particular to a three-layer co-embossed material of a lightweight renewable material and a preparation process thereof. Background Art

[0002] In the field of material processing and surface treatment, embossing technology is an important means of decoration and functional improvement, and is widely used in many industries such as textiles, packaging, building materials, and automotive interiors. Embossing generally uses steel plates or embossing rollers engraved with different patterns to press patterns or simulate animal leather grain patterns on the leather surface or textile surface. It was originally used to cover up the original grain defects of the leather surface to improve the use value, and is now mostly used to improve the appearance and aesthetics. The embossing process is based on different molds. There are two types: atmosphere plate type and roller type. The plate type embossing machine is the same as the plate type ironing machine, including a heated upper plate engraved with patterns and a lower plate. The upper and lower plates are contacted and ironed to emboss the leather surface in the middle. The roller embossing machine device consists of a heated roller engraved with patterns and a pressure roller. The leather is embossed with patterns when it passes between the two rotating rollers.

[0003] However, whether it is a plate embossing machine or a roller embossing machine, based on the traditional embossing process, it is often limited to the processing of single-layer and double-layer materials. However, based on the national green environmental protection requirements, after renewable materials such as recycled TPO, recycled PVC or recycled TPU are applied to single-layer or double-layer embossed materials, their aesthetics are always insufficient. Summary of the invention

[0004] In order to realize the utilization of renewable materials and improve the aesthetics of embossed materials, the present application provides a three-layer co-embossed material of lightweight renewable materials and a preparation process.

[0005] In the first aspect, the present application provides a preparation process of a three-layer co-laminated embossed material of a lightweight renewable material, using the following technical solution: A preparation process of a three-layer co-laminated embossed material made of lightweight renewable materials, wherein the three-layer co-laminated embossed material comprises a surface layer, an intermediate layer and a bottom layer, wherein the intermediate layer is prepared by mixing and foaming recycled waste materials with polyolefin foaming materials; It includes the following steps: S1. Decontamination and drying of the surface layer, the middle layer and the bottom layer are performed, and adhesive is applied to the side of the middle layer close to the surface layer and the side of the bottom layer close to the middle layer; S2. The side of the surface layer close to the middle layer, the side of the middle layer and the bottom layer not coated with adhesive are heated by a heating roller. After heating, the co-lamination and embossing are completed simultaneously by extrusion between the back roller and the embossing roller to obtain a three-layer co-lamination embossed material.

[0006] By adopting the above technical solution and the three-layer co-lamination process of the present application, the recycled waste layer can be wrapped to improve the aesthetics, and the foaming layer of post-consumer and recycled materials is used as the middle layer, which reduces the density of the material and realizes the recyclability and lightweight of the material; and by co-laminating the three layers and performing embossing operations at the same time, the production efficiency is greatly improved, meeting the national green environmental protection requirements.

[0007] Preferably, a heating lamp is provided on a side of the surface layer away from the middle layer for heating.

[0008] By adopting the above technical solution, the embossing effect of the surface layer can be improved and the boundary of the embossed pattern can be clearer.

[0009] Preferably, a heating lamp is provided above the side of the intermediate layer and the bottom layer coated with the adhesive for heating.

[0010] By adopting the above technical solution, the adhesive can be kept in liquid state, maintain viscosity, delay the solidification time of the adhesive, and achieve a better co-sticking effect.

[0011] In the second aspect, the present application provides a three-layer co-embossed material of a lightweight renewable material, which adopts the following technical solution: A three-layer co-laminated embossed material made of a lightweight renewable material, wherein the three-layer co-laminated embossed material is prepared by the preparation process of the three-layer co-laminated embossed material made of a lightweight renewable material according to any one of claims 1-3.

[0012] By adopting the above technical solution, the production efficiency and product qualification rate of the three-layer co-lamination embossed material produced by the three-layer co-lamination process provided by the present application are both high.

[0013] Preferably, the recycled waste accounts for ≤70% of the weight of the intermediate layer, and the preparation method of the intermediate layer is as follows: The recycled waste is crushed to obtain a crushed material with a crushed particle size of ≤3 mm, and the recycled waste crushed material and a polyolefin foaming material are mixed and foamed; The polyolefin foaming material comprises the following raw materials in parts by weight: 45-55 parts of polyolefin elastomer, 35-45 parts of metallocene polyethylene, 35-45 parts of styrene-butadiene block polymer, 4-7 parts of microsphere foaming agent, 0.3-0.7 parts of foaming promoter, 0.8-1.2 parts of crosslinking agent, 0.3-0.6 parts of auxiliary crosslinking agent, 0.3-0.7 parts of surfactant and 0.05-0.5 parts of anti-aging agent; The surfactant is prepared by compounding poloxamer and sodium dodecylbenzene sulfonate, and the weight ratio of the poloxamer to the sodium dodecylbenzene sulfonate is (1-5):1.

[0014] By adopting the above technical scheme, when polyolefin is foamed, due to the influence of interfacial energy, the bubbles at the edge of the recycled pulverized material are larger, so that there is a large spatial separation surface between the recycled pulverized material and the polyolefin foaming material, so that the obtained three-layer co-applied embossed material has poor mechanical properties. Poloxamer is a new type of high molecular non-ionic surfactant, which is a polyoxyethylene polyoxypropylene ether block copolymer, and is mostly used as a pharmaceutical excipient, such as an emulsifier and stabilizer for intravenous emulsions. The inventor of the present application compounded it with sodium dodecylbenzene sulfonate and applied it to the middle layer polyolefin foaming system and found that it has excellent compatibility with the system, can play an excellent foam stabilizing role, and can adjust the foaming uniformity. The bubbles at the edge of the recycled pulverized material are uniform, the spatial separation degree of the edge of the recycled pulverized material is greatly reduced, and the mechanical properties of the three-layer co-applied embossed material are improved. The mechanical properties of the three-layer co-applied embossed material are greatly improved by controlling the particle size of the surfactant and the recycled pulverized material. The weight ratio of poloxamer to sodium dodecylbenzene sulfonate is a key factor affecting the mechanical properties of the three-layer co-embossed material. When the weight ratio of poloxamer to sodium dodecylbenzene sulfonate is within this range, the synergistic effect between the two substances is better.

[0015] Preferably, the recycled crushed material is soaked in a hydroxy silane coupling agent solution and then mixed with a polyolefin foaming material for foaming.

[0016] By adopting the above technical scheme, the compatibility between the recycled crushed material and the polyolefin foaming material can be improved after the recycled crushed material is treated with a silane coupling agent. In addition, the silane coupling agent, as an organic silicon substance, has a certain defoaming effect, which can eliminate larger bubbles in contact with the recycled crushed material, thereby reducing the separation between the recycled crushed material and the polyolefin foaming material, making the integrity of the middle layer higher, and thus making the mechanical properties of the three-layer co-embossed material stronger.

[0017] Preferably, the adhesive is polyurethane foam.

[0018] By adopting the above technical scheme, the polyolefin foaming agent is bonded by polyolefin foaming. When the back roller and the embossing roller are extruded, the polyolefin foam is co-applied. Under the extrusion, the polyolefin foam expands and impacts the surface layer, the middle layer and the bottom layer, so that the adhesive is closely attached to each layer, thereby making the integrity of the three-layer co-applied embossed material better and the peeling strength excellent.

[0019] Preferably, the thickness of the surface layer is 0.1-0.4 mm, the thickness of the middle layer is 0.1-0.6 mm, and the thickness of the bottom layer is 0.1-0.4 mm.

[0020] Preferably, the surface layer is TPO single film, PVC single film or TPU single mold; the bottom layer is TPO single mold, base fabric layer, polyolefin foam layer or polyolefin foam layer; the recycled waste is one or more of recycled TPO, recycled PVC and recycled TPU.

[0021] In summary, the present application includes at least one of the following beneficial technical effects: 1. Through the three-layer co-lamination process of the present application, the recycled waste layer can be wrapped to improve the aesthetics, and the foaming layer of post-consumer and recycled materials is used as the middle layer, which reduces the density of the material and realizes the recyclability and lightweight of the material; and through the three-layer co-lamination and simultaneous embossing operations, the production efficiency is greatly improved, meeting the national green environmental protection requirements.

[0022] 2. When polyolefin is foamed, due to the influence of interfacial energy, the bubbles at the edge of the recycled pulverized material are larger, resulting in a larger spatial separation surface between the recycled pulverized material and the polyolefin foaming material, which makes the mechanical properties of the three-layer co-embossed material poor. Poloxamer is a new type of high molecular non-ionic surfactant, a polyoxyethylene polyoxypropylene ether block copolymer, and is mostly used as a pharmaceutical excipient, such as an emulsifier and stabilizer for intravenous emulsions. The inventors of this application compounded it with sodium dodecylbenzene sulfonate and applied it to the middle layer polyolefin foaming system and found that it has excellent compatibility with the system, can play an excellent role in stabilizing foams, and can adjust the uniformity of foaming. The bubbles at the edge of the recycled pulverized material are uniform, the degree of spatial separation at the edge of the recycled pulverized material is greatly reduced, and the mechanical properties of the three-layer co-embossed material are improved.

[0023] 3. In the present application, recycled elastic waste is mixed with polyurethane for foaming, and the three-layer co-laminated embossed material is prepared through the co-laminated process of the present application. When the embossed pattern boundary is clear and complete and meets the requirements, its peel strength can reach 17.8kg / mm, and the tensile strength can reach 79MPa. At the same time, its wear resistance is excellent. DETAILED DESCRIPTION

[0024] The present application is further described in detail below in conjunction with the specific contents.

[0025] raw material The raw materials used in the examples of this application can all be purchased commercially. Example

[0026] Example 1 A three-layer co-embossed material of lightweight renewable materials, comprising a surface layer, an intermediate layer and a bottom layer, and the preparation process thereof is as follows: S1, the intermediate layer is made of recycled waste by polyolefin foaming, and the preparation method thereof is as follows: The recycled TPO waste is washed, dried, and crushed to a particle size of less than 3 mm, and the recycled TPO crushed material and polyolefin foaming material are mixed and foamed, and the weight ratio of the recycled TPO crushed material to the polyolefin foaming material is 5:3; wherein the polyolefin foaming material includes 50 kg of polyolefin elastomer, 40 kg of metallocene polyethylene, 40 kg of styrene-butadiene block polymer, 6 kg of microsphere foaming agent, 0.5 kg of foaming promoter, 1 kg of cross-linking agent, 0.4 kg of auxiliary cross-linking agent, 0.5 kg of surfactant and 0.1 kg of anti-aging agent; Among them, the polyolefin elastomer uses POE, and its brand is Mitsui Chemicals DF740; the metallocene polyethylene is polyethylene prepared by metallocene technology, with an average molecular weight of 45000; the styrene-butadiene block polymer is hot melt grade, with a brand of 3540F; the surfactant is a mixture of poloxamer and sodium dodecylbenzene sulfonate, with a weight ratio of 3:1, and the average molecular weight of poloxamer is 8350, referred to as F68; the microsphere foaming agent is Matsumoto microsphere foaming agent F-36; the foaming promoter is zinc stearate; the crosslinking agent is diisopropyl peroxide; the auxiliary crosslinking agent is diallyl terephthalate; the anti-aging agent is antioxidant 1010; The specific foaming method is as follows: the raw materials of the polyolefin foaming material are mixed, foamed in a high-temperature furnace, the foaming temperature is 155°C, and after the foaming is completed, it is extruded through the discharge end of a single-screw extruder, granulated, and a recycled waste foaming material is obtained, and the extrusion temperature is 160°C; The recycled waste foam material is heated to 170°C for melt extrusion to form a film with a thickness of 0.4 mm, i.e., the middle layer; S2. The surface layer uses a TPU single film with a thickness of 0.3 mm, which is a TPU hot melt adhesive film; the bottom layer uses a TPO single film with a thickness of 0.1 mm; after the surface layer, the middle layer and the bottom layer are decontaminated and dried, the adhesive is applied to the side of the middle layer close to the surface layer and the side of the bottom layer close to the middle layer; S3. The surface layer, the middle layer and the bottom layer are heated by heating rollers respectively. After heating, the surface layer, the middle layer and the bottom layer are extruded and co-laminated by a back roller and an embossing roller, and the embossing roller embosses the surface layer at the same time. In addition, a heating lamp is provided on the side of the surface layer away from the heating roller for heating, so that the embossing effect of the surface layer can be better and the boundary of the embossed pattern can be clearer. Heating lamps are provided above the adhesive-coated side of the middle layer and the bottom layer to keep the adhesive in a liquid state and maintain viscosity, so as to achieve a better co-lamination effect. The temperature of the heating roller and the back roller is 80°C, and the power of the heating lamp is 1000W.

[0027] Example 2 A three-layer co-embossed material of a lightweight renewable material is different from Example 1 in that its recycled TPO crushed material is soaked in a silane coupling agent ethanol solution with a mass fraction of 10%, the silane coupling agent is bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane, filtered, dried, and then mixed with polyolefins for foaming, and the remaining steps are the same as Example 1.

[0028] Example 3 A three-layer co-embossed material made of lightweight renewable materials is different from Example 2 in that the weight ratio of poloxamer and sodium dodecylbenzene sulfonate is 1:1, and the remaining steps are the same as Example 2.

[0029] Example 4 A three-layer co-embossed material made of lightweight renewable materials is different from Example 2 in that the weight ratio of poloxamer to sodium dodecylbenzene sulfonate is 5:1, and the remaining steps are the same as those in Example 2.

[0030] Example 5 A three-layer co-embossed material made of lightweight renewable materials is different from Example 2 in that the weight ratio of the recycled TPO crushed material to the polyolefin foamed material is 3:3, and the remaining steps are the same as Example 2.

[0031] Example 6 A three-layer co-embossed material made of lightweight renewable materials is different from Example 2 in that the weight ratio of the recycled TPO crushed material to the polyolefin foamed material is 7:3, and the remaining steps are the same as Example 2.

[0032] Example 7 A three-layer co-embossed material made of a lightweight renewable material, which is different from Example 6 in that the thickness of the middle layer is 0.6 mm, and the remaining steps are the same as Example 6.

[0033] Example 8 A three-layer co-embossed material of a lightweight renewable material is different from Example 2 in that the recycled TPO crushed material is replaced by recycled PVC crushed material of the same crushed particle size, and the remaining steps are the same as Example 2.

[0034] Example 9 A three-layer co-embossed material of a lightweight renewable material is different from Example 2 in that the recycled TPO crushed material is replaced by recycled TPU crushed material of the same crushed particle size, and the remaining steps are the same as Example 2.

[0035] Example 10 A three-layer co-embossed material made of a lightweight renewable material is different from Example 2 in that the middle layer and the bottom layer are not heated by heating lamps, and the remaining steps are the same as those of Example 2.

[0036] Comparative Example Comparative Example 1 A three-layer co-embossed material made of a lightweight renewable material is different from Example 1 in that poloxamer is not added to the surfactant, and the remaining steps are the same as those of Example 1.

[0037] Comparative Example 2 A three-layer co-embossed material made of a lightweight renewable material is different from Example 1 in that sodium dodecylbenzene sulfonate is not added to the surfactant, and the remaining steps are the same as those of Example 1.

[0038] Comparative Example 3 A three-layer co-embossed material made of lightweight renewable materials is different from Example 1 in that no surfactant is added to the polyolefin foam material during the preparation of the intermediate layer, and the remaining steps are the same as those of Example 1.

[0039] Comparative Example 4 A three-layer co-embossed material made of a lightweight renewable material, which is different from Example 6 in that the thickness of the middle layer is 0.7 mm, and the remaining steps are the same as Example 6.

[0040] Comparative Example 5 A three-layer co-embossed material made of lightweight renewable materials is different from Example 1 in that the particle size range of its TPO crushed material is 3-7 mm, and the remaining steps are the same as Example 1.

[0041] Performance testing Detection method / test method Three-layer co-embossed materials were prepared according to the preparation processes in Examples 1-10 and Comparative Examples 1-5, and then tested according to the following testing methods.

[0042] Peel strength: Cut the three-layer embossed material into samples of 25mm×150mm and test them with a tensile machine at a test speed of 100mm / min; Wear resistance: The test was conducted according to the test method in QBT4195-2011, using an H-22 grinding wheel, a load of 1kg, and 400 revolutions to detect whether the surface was worn through to expose the middle layer.

[0043] Tensile strength: The tensile test was carried out using a universal testing machine at a tensile speed of 10 mm / min.

[0044] Table 1 Test results of Examples 1-10 and Comparative Examples 1-5 It can be seen from Examples 1-10 and Comparative Examples 1-5, as well as the test data in Table 1, that the present application foams the recycled elastic waste by mixing it with polyurethane, and through the co-lamination process of the present application, the three-layer co-lamination embossed material obtained has clear and complete embossed pattern boundaries and meets the requirements, and its peel strength can reach 17.8kg / mm, and its tensile strength can reach 79MPa, while its wear resistance is excellent; through multi-layer co-lamination and exquisite embossing treatment, the appearance and market competitiveness of the product are greatly improved, meeting the national green environmental protection requirements; the foaming layer of post-consumer and recycled materials is used as the middle layer, which reduces the density of the material and realizes the recyclability and lightweight of the material.

[0045] When polyolefin is foamed, due to the influence of interfacial energy, the bubbles at the edge of the recycled pulverized material are larger, so that there is a large spatial separation surface between the recycled pulverized material and the polyolefin foaming material, so that the obtained three-layer co-applied embossed material has poor mechanical properties. Poloxamer is a new type of high molecular non-ionic surfactant, which is a polyoxyethylene polyoxypropylene ether block copolymer, and is mostly used as a pharmaceutical excipient, such as an emulsifier and stabilizer for intravenous emulsions. The inventor of the present application compounded it with sodium dodecylbenzene sulfonate and applied it to the middle layer polyolefin foaming system and found that it has excellent compatibility with the system, can play an excellent foam stabilizing role, and can adjust the foaming uniformity. The bubbles at the edge of the recycled pulverized material are uniform, the spatial separation degree of the edge of the recycled pulverized material is greatly reduced, and the mechanical properties of the three-layer co-applied embossed material are improved. This can be verified by the test data of Example 1 and Comparative Example 3. Combined with the test data of Comparative Examples 1-2, poloxamer and sodium dodecylbenzene sulfonate have a synergistic effect, and need to be added at the same time to achieve the expected effect.

[0046] Combined with the test data of Examples 1-2, it can be seen that after the recycled crushed material is treated with a silane coupling agent, the compatibility between the recycled crushed material and the polyolefin foaming material can be improved, and the silane coupling agent, as an organic silicon substance, has a certain defoaming effect, which can eliminate larger bubbles in contact with the recycled crushed material. In addition, the present application uses a hydroxy silane coupling agent, which can participate in the polyolefin foaming reaction, so that the surface of the recycled waste material can participate in the polyolefin foaming reaction in situ; thereby reducing the separation between the recycled crushed material and the polyolefin foaming material, making the integrity of the middle layer higher; thereby making the mechanical properties of the three-layer co-embossed material obtained stronger.

[0047] Combined with the test data of Examples 2-4, it can be seen that the weight ratio of poloxamer to sodium dodecylbenzene sulfonate is a key factor affecting the mechanical properties of the three-layer co-embossed material. When the weight ratio of poloxamer to sodium dodecylbenzene sulfonate is 3:1, the synergistic effect between the two substances is optimal.

[0048] The test data of Example 2 and Examples 5-6 show that the higher the amount of recycled crushed material added in the middle layer, the lower the mechanical properties of the three-layer co-embossed material. Considering its mechanical properties, the amount added should not exceed 70%. Combining Example 7 and Comparative Example 4, when the weight percentage of recycled crushed material added is 70%, the thickness of the middle layer should not exceed 0.6 mm.

[0049] It can be seen from the test data of Example 2 and Examples 8-9 that the recycled crushed material is recycled TPO, recycled PVC or recycled TPU, all of which can produce a three-layer co-embossed material with excellent mechanical properties.

[0050] It can be seen from the test data of Example 2 and Example 10 that the heating lamp tube can make the bonding force between the surface layer, the middle layer and the bottom layer stronger.

[0051] It can be seen from the test data of Example 1 and Comparative Example 5 that the particle size of the recycled crushed material should not be too large. When the particle size is large, the wettability and wrapping properties of the polyolefin foam material on the recycled crushed material are insufficient, and the mechanical properties of the obtained three-layer co-embossed material are poor.

[0052] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. A process for preparing a three-layer co-embossed material of a lightweight renewable material, characterized by: The three-layer co-embossed material comprises a surface layer, a middle layer and a bottom layer, wherein the middle layer is made by mixing and foaming recycled waste with polyolefin foaming material; It includes the following steps: S1. Decontamination and drying of the surface layer, the middle layer and the bottom layer are performed, and adhesive is applied to the side of the middle layer close to the surface layer and the side of the bottom layer close to the middle layer; S2. The side of the surface layer close to the middle layer, the side of the middle layer and the bottom layer not coated with adhesive are heated by a heating roller. After heating, the co-lamination and embossing are completed simultaneously by extrusion between the back roller and the embossing roller to obtain a three-layer co-lamination embossed material.

2. The process for preparing a three-layer co-laminated embossed material made of a lightweight renewable material according to claim 1, characterized in that: A heating lamp is also provided on a side of the surface layer away from the middle layer for heating.

3. The process for preparing a three-layer co-laminated embossed material made of a lightweight renewable material according to claim 1, characterized in that: A heating lamp is arranged above the side of the intermediate layer and the bottom layer coated with the adhesive for heating.

4. A three-layer co-embossed material made of lightweight renewable materials, characterized by: The three-layer co-applied embossed material is prepared by the preparation process of the three-layer co-applied embossed material of any one of claims 1-3.

5. The three-layer co-embossed material of a lightweight renewable material according to claim 4, characterized in that: The recycled waste accounts for ≤70% of the weight of the intermediate layer. The preparation method of the intermediate layer is as follows: The recycled waste is crushed to obtain a crushed material with a crushed particle size of ≤3 mm, and the recycled waste crushed material and a polyolefin foaming material are mixed and foamed; The polyolefin foaming material comprises the following raw materials in parts by weight: 45-55 parts of polyolefin elastomer, 35-45 parts of metallocene polyethylene, 35-45 parts of styrene-butadiene block polymer, 4-7 parts of microsphere foaming agent, 0.3-0.7 parts of foaming promoter, 0.8-1.2 parts of crosslinking agent, 0.3-0.6 parts of auxiliary crosslinking agent, 0.3-0.7 parts of surfactant and 0.05-0.5 parts of anti-aging agent; The surfactant is prepared by compounding poloxamer and sodium dodecylbenzene sulfonate, and the weight ratio of the poloxamer to the sodium dodecylbenzene sulfonate is (1-5):

1.

6. The three-layer co-embossed material of a lightweight renewable material according to claim 5, characterized in that: The recycled crushed material is soaked in a hydroxy silane coupling agent solution and then mixed with a polyolefin foaming material for foaming.

7. The three-layer co-embossed material of a lightweight renewable material according to claim 4, characterized in that: The adhesive is polyurethane foam.

8. The three-layer co-embossed material of lightweight renewable material according to claim 4, characterized in that: The thickness of the surface layer is 0.1-0.4 mm, the thickness of the middle layer is 0.1-0.6 mm, and the thickness of the bottom layer is 0.1-0.4 mm.

9. The three-layer co-embossed material of a lightweight renewable material according to claim 4, characterized in that: The surface layer is a TPO single film, a PVC single film or a TPU single mold; the bottom layer is a TPO single mold, a base fabric layer, a polyolefin foam layer or a polyolefin foam layer; the recycled waste is one or more of recycled TPO, recycled PVC and recycled TPU.

Citation Information

Patent Citations

  • Glycyrrhizic acid, biogastrone acid or its salt, derivative temperature sensing gel rubber, preparation method and application thereof

    CN101292952A

  • Preparation technology of waterproof roll material with long serivce life

    CN102168383A

  • Thermoplastic foaming polyurethane fiber board, production method and uses thereof

    CN103072346A

  • Biodegradable medical hemostatic sponge and preparation method thereof

    CN104693476A

  • Improved abiraterone acetate nanocrystal oral preparation and preparation method thereof

    CN114948885A